Transient liver elastography in the follow-up of Fontan patients: results of a nation wide survey in Germany - Meyer, Zora; Haas, Nikolaus; Mühlberg, Richard; Braun, Annabell; Fischer, Markus; Mandilaras, Guido (Frontiers in Pediatrics, 2023)
Introduction: Fontan-palliated patients are at risk for the development of Fontan-associated liver disease (FALD). Currently, there is no consensus on how to stage FALD. Transient elastography (TE) is a rapid, non-invasive method to assess FALD and liver fibrosis. Method: To assess the availability and conditions of using TE to monitor liver disease in Fontan patients in german centers for pediatric cardiology and to propose the introduction of a standardized national protocol for the monitoring of liver disease, we developed a questionnaire. Results: In total, 95 valid questionnaires were collected. Only 20% of the centers offer the TE investigation directly. Most of the centers transfer the patients to another department or center (40%) or didn´t offer TE (40%). In only 2.6% of the centers TE is performed directly by the cardiologist. Most of the centers transfer the patients to a other department. In 29.2% TE is performed only at a certain age of the patients and in 27.7% it is performed if the patients present symptoms of failing Fontan. In only 13.9% of the centers TE is proposed in all the Fontan patients on a routine basis. Most often TE is performed only from the beginning of the adolescence. In the majority of answers it was not known if the patients are fasting for the examination (68%) or not and if the TE examination had to be performed in a specific breathing phase during TE (Inspiration/Expiration, 90%). In the majority, TE is not offered routinely (46.9%) . Discussion: To date in Germany, TE is only used in a few numbers of centers specialized in Fontan follow-up. A standardized protocol to use TE is currently not existing. With regard to the feasibility of the examination, it is evident that TE is a quick, cheap and easy method to distinguish between cases with and without progressive FALD. This makes TE a useful and prognostic tool for screening of liver disease and to failing Fontan circulation. Conclusion: We propose a systematic TE evaluation of possible liver congestion and fibrosis, as a part of the routine follow-up of Fontan patients.